Inspiratory Muscle Training in Pulmonary Arterial Hypertension. Issue 3 (May 2015) - Saglam, Melda; Arikan, Hulya; Vardar-Yagli, Naciye; Calik-Kutukcu, Ebru; Inal-Ince, Deniz; Savci, Sema; Akdogan, Ali; Yokusoglu, Mehmet; Kaya, Ergun Baris; Tokgozoglu, Lale
<x xml:space="preserve">Abstract</x> PURPOSE: The purpose of this study was to investigate the effects of inspiratory muscle training (IMT) on functional capacity, respiratory muscle strength, pulmonary function, quality of life, and fatigue and dyspnea perception in patients with pulmonary arterial hypertension (PAH). METHODS: Twenty-nine clinically stable PAH patients were included in this study. These patients were randomly assigned to a 6-week IMT program (14 patients) or to a sham IMT protocol (15 patients). Before and after the treatment, pulmonary function, respiratory muscle strength, functional capacity, dyspnea and fatigue perception, and quality of life were evaluated. RESULTS: There were significant increases in maximal inspiratory and expiratory pressure, forced expiratory volume in 1 second (% predicted) and 6-minute walk distance in the IMT group compared with the control group (P < .05). There were significant decreases in the Fatigue Severity Scale score, Modified Medical Research Council dyspnea scores, and Nottingham Health Profile emotional reactions subscale in the IMT group compared with the control group (P < .05). CONCLUSIONS: Inspiratory muscle training promotes significant improvements in respiratory muscle strength and functional capacity, thus resulting in a reduction of dyspnea during activities of daily living and less fatigue in PAH patients. Inspiratory muscle training is a clinically practical treatment for PAH without any complications.